Лекарственные растения в народной медицине - Махлаюк Виталий Петрович (Нива России, 1992)
Экземпляры: КХ (20060523) / Инвентарный номер: 1010016 / Цена: / Сис.шифр: 53.525 / Авт.знак: М 36 / ГРНТИ: 68 / ББК: 42.143